MOTIVASI BELAJAR IPA SISWA DALAM PEMBELAJARAN FISIKA MELALUI MEDIA KOMIK PADA MATERI CAHAYA DI KELAS VIII SMPN 21 PEKANBARU - Roni Wijaya; Fakhruddin '; Syahril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract This research is arms to determine the increase in student motivationSMPN 21 Pekanbaru using comic as media of learning in the light subject. The sampelof this research was 37 students of VIII6 grade and 37 students of VIII7 grade. Inconducting the research, the researcher used Pre-experimental as the method ofresearch with Nonequivalent Control design. The instrument of this research wasstudent learning motivation questionnaire which consists of 50 questions which isconsist of 25 positive questions and 25 negative questions. The Data was analized usingdescriptive analysis thecnique by the increaseof students learning motivation from thegain score and using inferential with t test by SPSS.Based on t test which means aredifferent learning motivation between experiment class and control class with sig result0,01<0,05, it is proven by descriptive the incrising of learning descritive analized finalmotivation students on the experiment grade with middle low category by the incrisingof students learning motivation with Gain 0,08. It can that therefore be conclude thatused comic as learning media can increasestudents motivation learning on light subjectat VIII grade SMPN 21Pekanbaru.Keywords:Learning Motivation, Media Comic2MOTIVASI BELAJAR IPA SISWA DALAM PEMBELAJARAN